Characterization of suspended sand concentrations in the Yangtze River Estuary and adjacent waters - Luan, Kuifeng; Li, Hui; Pan, Yujia; Wang, Zhenhua; Xu, Hang; Zhu, Weidong; Wang, Jie; Wan, Haixia; You, Xinyi (Frontiers in Marine Science, 2023)
The study on the distribution characteristics of suspended sediment concentration (SSC) in estuaries is an important subject in the study of estuaries and coasts, which has important theoretical significance and practical value. In order to fully understand the characteristics of SSC in the Yangtze River Estuary and its adjacent waters, this paper uses fixed vertical observation data and navigation type large area observation data as data sources to analyze the distribution characteristics of SSC in the Yangtze River Estuary and its adjacent waters under different tidal current states and its vertical profile characteristics. It discusses the impact of tidal current velocity on SSC and the changes of SSC in the Yangtze River Estuary and its adjacent waters from 2018 to 2020. And the applicability of the Rouse and Soulsby formulas in the Yangtze River Estuary and its adjacent waters was verified. It was found that the Rouse and Soulsby models have high applicability in the study area, and the prediction accuracy based on the Li's Soulsby model is higher. This study provides effective support for carrying out marine forecasting, analysis and evaluation, and provides theoretical basis for carrying out analysis of the current situation of estuarine mudflat resources and prediction of the evolution trend. It plays an important role in scientific and comprehensive research